First- and second-generation design and engineering students: experience, attainment and factors influencing them to attend university. Issue 1 (2nd January 2018) - Hunt, Clive; Collins, Bethan; Wardrop, Alex; Hutchings, Maggie; Heaslip, Vanessa; Pritchard, Colin
ABSTRACT: Challenges for students who are 'first-in-family' to attend university have been discussed within widening participation discourse. However, in the UK, 'first-in-family' or first-generation students have frequently been conflated with those experiencing poverty or from lower socio-economic groups. This research integrated survey data with assessment data from final-year design and engineering students in a UK university to examine students' attainment, the influences on why students decide to attend university and students' experiences during their degree programmes. Analysis of the data showed variations in the reasons for first- and second-generation students wanting to go to university, particularly a significant difference in the influence of parents. First-generation students described significantly less parental influence on the decision to attend university than second- or subsequent-generation students. Smaller differences in students' experiences and attainment in university were also noted. Whilst first-generation students reported differences in study habits, their attainment was, on average, marginally higher than that of their peers. Building on others' theoretical work, which suggests the importance of social capital within higher education (HE), this research highlights the difference in social influences on both university application and expectations of university for those with and without a family history of tertiary education. Further research is needed to explore, in larger samples, whether the social influences on individuals' perception of HE are in turn shaped by whether or not their parents attended university, and further, what impact this may have, not only on degree outcomes but also on the broader benefits typically associated with graduate experience.